Mathematical Demoeconomy : Integrating Demographic and Economic Approaches. - Popkov, Yuri S. (De Gruyter, 2014)
This monograph aspires to lay the foundations of a new scientific discipline, demoeconomics, representing the synthesis of demography and spatial economics. This synthesis is performed in terms of interaction between population and its economic activity. Demoeconomic systems are studied involving the macrosystems approach which combines the generalized entropy maximization principle and the local equilibria principle.